A congestion-aware and robust multicast protocol in SDN-based data center networks. (1st October 2017) - Zhu, Tingwei; Feng, Dan; Wang, Fang; Hua, Yu; Shi, Qingyu; Xie, Yanwen; Wan, Yong
Abstract: Continuously enriched distributed systems in data centers generate much network traffic in push-style one-to-many group mode, raising new requirements for multicast transport in terms of efficiency and robustness. Existing reliable multicast solutions, which suffer from low robustness and inefficiency in either host-side protocols or multicast routing, are not suitable for data centers. In order to address the problems of inefficiency and low robustness, we present a sender-initiated, efficient, congestion-aware and robust reliable multicast solution mainly for small groups in SDN-based data centers, called MCTCP. The main idea behind MCTCP is to manage the multicast groups in a centralized manner, and reactively schedule multicast flows to active and low-utilized links, by extending TCP as the host-side protocol and managing multicast groups in the SDN-controller. The multicast spanning trees are calculated and adjusted according to the network status to perform a better allocation of resources. Our experiments show that, MCTCP can dynamically bypass the congested and failing links, achieving high efficiency and robustness. As a result, MCTCP outperforms the state-of-the-art reliable multicast schemes. Moreover, MCTCP improves the performance of data replication in HDFS (Hadoop Distributed File System) compared with the original and TCP-SMO (an alternative reliable multicast scheme) based ones, e.g., achieves up to 1.5 × and 1.1 × improvements in terms of throughput, respectively. Abstract : Graphical abstract: Abstract : Highlights: A congestion-aware transport-layer reliable multicast transmission scheme in SDN-based data centers is proposed. Achieving Routing efficiency and Robustness by reactively scheduling multicast flows at the SDN controller. Multicast-based data replication is implemented in HDFS using the proposed multicast scheme.